THE CHALLENGE OF BEING A TEACHER IN INDUSTRIAL REVOLUTION 4.0 - Mukhtar Efendi (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2026)
The aims of study is to describe the challenges faced by teachers in facing the changes in the era of globalization and technology in the Industrial Revolution 4.0 era at Darussalamah Junior High School (SMPS Darussalamah). The research method used was descriptive qualitative and refers to a case study. Data collection was conducted through observation, interviews, and documentation. Data validity was validated using diligent observation and triangulation of techniques and sources. The results of the study indicate that teachers face several challenges in the changing era of the Industrial Revolution 4.0 era at Darussalamah Junior High School. One challenge is the need for digital literacy, where teachers must improve their understanding and knowledge of technology to implement this knowledge in the teaching process. Another challenge is the ability of teachers to innovate in teaching methods in accordance with existing developments. Another challenge comes from students, where student morale has been eroded due to changes in technological globalization, and students' social engagement with their environment has also been eroded. This includes not only fellow students but also a lack of respect for their responsibilities as learners. Keywords: Challenges, Teachers, Industry 4.0 Keywords: three to five words, italic, alphabetically arranged